INDICATOR DETERMINATION OF SELECTION FOR IMPROVING SOYBEAN YIELD - Sakka Samudin; Alfian Samudin; Zainuddin Basri (Tadulako University, 2014)
The need for soybean increasing every year causes soybean imports to be done continually, so an effort to increase the production must be done to reduce dependency on imported soybean. This study aims to determine the characters that can be used as an indicator of selection to increase soybean yields. The study was conducted in the village of Sa'atu, Coastal Poso Subdistrict, Poso Regency, Central Celebes Province, from January to April 2011. Using a randomized block design (RBD) with 30 genotypes (varieties) as the treatments that were repeated 3 times, so it obtained 90 units of experimental plots. The observed variables were plant height at harvesting time, flowering age, harvesting age, number of pods per plant, number of seeds per pod, number of productive branches per plant, total weight of pods per plot, weight of 100 seeds and yield of seeds. The results showed that plant height at harvesting time, harvesting age and number of seeds per pod have genetic variability coefficients that were moderate while the other traits were high. The number of pods per clump and the number of seeds per pod have moderate heritability values while the other traits were high enough. Harvesting age has a significant negative genetic correlation with the yield while the number of productive branches, total weight of pods per plot and weight of 100 seeds have significant positive genetic correlations with soybean yields. Weight of pods per plot is a trait that has high direct effect on and significant positive correlation with the yields so it can be used as an indicator of trait selection to improve soybean yields.